A cochlear-bone wave can yield a hearing sensation as well as otoacoustic emission - Tchumatchenko, Tatjana; Reichenbach, Tobias (Nature Communications, 2014)
A hearing sensation arises when the elastic basilar membrane inside the cochlea vibrates. The basilar membrane is typically set into motion through airborne sound that displaces the middle ear and induces a pressure difference across the membrane. A second, alternative pathway exists, however: stimulation of the cochlear bone vibrates the basilar membrane as well. This pathway, referred to as bone conduction, is increasingly used in headphones that bypass the ear canal and the middle ear. Furthermore, otoacoustic emissions, sounds generated inside the cochlea and emitted therefrom, may not involve the usual wave on the basilar membrane, suggesting that additional cochlear structures are involved in their propagation. Here we describe a novel propagation mode within the cochlea that emerges through deformation of the cochlear bone. Through a mathematical and computational approach we demonstrate that this propagation mode can explain bone conduction as well as numerous properties of otoacoustic emissions. © 2014 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2021-02-25